The Relationship Between Sleep Duration and Hypertension Incidence in Civil Servants Aged 30 to 60 Years - Aulia Wiratama Putra (Riviera Publishing, 2023)
Introduction: The adult prevalence of Hypertension increased significantly globally. Enhancement of this increase in a manner together with decline duration sleep. Some study has shown exists connection Between the duration of sleep with incident hypertension. To could understand exists relationship between-both of them needs to be conducted purposeful research-to know if the enhancement of high hypertension-is related to the duration of sleep. Method: The research uses studies of observational analytics with design cut following cross-include 169 civil servants in agriculture and communications Old Cianjur-between 30 to 60 years. Data were collected with a questionnaire about name age, breed gender, and duration sleep, and Sleep Duration and measurement pressure blood then based on criteria of The Seventh Report of The Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC7). Data analysis using SPSS for windows with the level the meaning used as big not enough from 0.05. Results: Data analysis using Chi-Square shows that exists a connection meaning-Among duration of sleep with hypertension body (p=0.015) in the Civil Service Service agriculture and communications Cianjur. Getting that duration of sleep is not enough to own connection with incident hypertension compared to civil servants who have sleep enough. Conclusion: Research this show that duration sleep related hypertension in PNS so expected Public especially civil servants understand the importance own duration of good sleep.